2022
DOI: 10.1021/acsomega.2c04042
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nickel Oxide Nanoparticles and Copper-Doped Nickel Oxide Nanocomposites Using Phytolacca dodecandra L’Herit Leaf Extract and Evaluation of Its Antioxidant and Photocatalytic Activities

Abstract: Nanotechnology research is emerging as cutting-edge technology, and nanoparticles (NPs) and nanocomposites (NCs) have played a significant role in the bioremediation and treatment of polluted water by organic and nonorganic materials. Nanoparticles produced by plant extracts are more stable and biocompatible in comparison with those produced by physical and chemical methods. This research focuses on the synthesis of NiO NPs and Cu–NiO NCs using Phytolacca dodecandra L’Herit (P.d) leaf extract and evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Notably, no additional peaks were observed in the pattern, indicating the high purity of the nanoparticles. The obtained indexed peak pattern matched well with the standard pattern (JCPDS # 96-101-0096) for NiO as already established in literature [26]. The reflections were indexed to the face-cantered cubic NiO phase, which is consistent with previously reported works in the literature.…”
Section: Anti-inflammatory Studysupporting
confidence: 89%
“…Notably, no additional peaks were observed in the pattern, indicating the high purity of the nanoparticles. The obtained indexed peak pattern matched well with the standard pattern (JCPDS # 96-101-0096) for NiO as already established in literature [26]. The reflections were indexed to the face-cantered cubic NiO phase, which is consistent with previously reported works in the literature.…”
Section: Anti-inflammatory Studysupporting
confidence: 89%
“…The degradation of MB dye is characterized by a gradual change in the color of the dye solution from blue to colorless along with a continuous decrease in MB absorption as the irradiation time increases (Figure ). This observation is consistent with previous studies on the photodegradation of MB by ZnO and metal-doped ZnO NPs . The degradation of MB dye was also studied in the presence of sunlight in the absence of catalysts.…”
Section: Resultsmentioning
confidence: 94%
“…The detailed procedures can be found elsewhere in the literature. 14,15 2.4. Synthesis of ZnO and Mg-Doped ZnO Nanoparticles.…”
Section: Collection and Extraction Of Plant Materialsmentioning
confidence: 99%
“…However, a peak at 452 cm −1 was noticed (which was absent in the CEML spectrum) that could be assigned to the NiO NP vibration. 49…”
Section: Resultsmentioning
confidence: 99%
“…However, a peak at 452 cm À1 was noticed (which was absent in the CEML spectrum) that could be assigned to the NiO NP vibration. 49 This fact suggested that the Cu became more corrosion resistant after CEML coating. 50 The maximum shift in OCP was observed for two layers of CEML, which could indicate that two layers of CEML offered the maximum corrosion resistance to Cu.…”
Section: Njc Papermentioning
confidence: 99%